Letter from John Jay Knox to James Curtis Booth - Knox, John Jay (1866)
Letter written by John Jay Knox Jr. (1828-1892), an American financier, government official, and primary author of the Coinage Act of 1873, to James Curtis Booth (1810-1888). Knox seeks to determine the relative values of the United States silver dollar, half dollar, and Mexican pesos.
Keywords: Booth, James Curtis, 1810-1888; Half-dollar; Money; Foreign exchange